The Dynamics of Family Life in Polygamous Practices: An Islamic Legal Perspective on Contemporary Indonesian Society - Akbar, Hikmal; Syauqi, M. Nabil (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
In a Muslim-majority country such as Indonesia, polygamy is governed by stringent legal frameworks that mandate obtaining court permission and providing evidence of equitable treatment toward all wives. This article examines the dynamics of polygamous household life in contemporary Indonesian Muslim society through the lens of Islamic law. While polygamy is legally and religiously permitted in Islam under conditions emphasizing justice and responsibility, its implementation often diverges from these ethical standards. Drawing on Qur’anic principles, Indonesian legal frameworks, and lived experiences, this study explores the challenges posed by unequal treatment, emotional and psychological impacts, and social stigma. Reformist Muslim scholars and women’s rights advocates have increasingly called for a reinterpretation of polygamy grounded in maqāṣid al-sharīʿa (the higher objectives of Islamic law), promoting justice, dignity, and gender equity. The article argues that ethical reconsideration through ijtihād is essential to align legal practice with the moral values of Islam in a modern context. Ultimately, the study highlights the need for a more humane, contextualized, and justice-oriented approach to Islamic family law in addressing polygamy today.